A High‐Performance Optical Memory Array Based on Inhomogeneity of Organic Semiconductors. Issue 13 (9th February 2018) - Pei, Ke; Ren, Xiaochen; Zhou, Zhiwen; Zhang, Zhichao; Ji, Xudong; Chan, Paddy Kwok Leung
Abstract: Organic optical memory devices keep attracting intensive interests for diverse optoelectronic applications including optical sensors and memories. Here, flexible nonvolatile optical memory devices are developed based on the bis[1]benzothieno[2, 3‐ d ;2′, 3′‐ d′ ]naphtho[2, 3‐ b ;6, 7‐ b′ ]dithiophene (BBTNDT) organic field‐effect transistors with charge trapping centers induced by the inhomogeneity (nanosprouts) of the organic thin film. The devices exhibit average mobility as high as 7.7 cm 2 V −1 s −1, photoresponsivity of 433 A W −1, and long retention time for more than 6 h with a current ratio larger than 10 6 . Compared with the standard floating gate memory transistors, the BBTNDT devices can reduce the fabrication complexity, cost, and time. Based on the reasonable performance of the single device on a rigid substrate, the optical memory transistor is further scaled up to a 16 × 16 active matrix array on a flexible substrate with operating voltage less than 3 V, and it is used to map out 2D optical images. The findings reveal the potentials of utilizing [1]benzothieno[3, 2‐ b ][1]benzothiophene (BTBT) derivatives as organic semiconductors for high‐performance optical memory transistors with a facile structure. A detailed study on the charge trapping mechanism in the derivatives of BTBT materials is also provided, which is closely related to the nanosprouts formed inside the organic active layer. Abstract : A high‐performance organic optical memory array is developed based on the structural inhomogeneity of bis[1]benzothieno[2, 3‐ d ;2′, 3′‐ d′ ]naphtho[2, 3‐ b ;6, 7‐ b′ ]dithiophene organic semiconductors with charge trapping centers induced by the nanosprouts in the thin film. The flexible 16 × 16 array can encrypt and store 2D optical images. The findings reveal the potential of utilizing [1]benzothieno[3, 2‐ b ][1]benzothiophene derivatives for high‐performance optical‐memory transistors with a facile structure.